EFEKTIVITAS MEDIA KOMIK FOTO UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Yuni Puspitasari; Anwar Senen (Universitas Muria Kudus, 2021)
The purpose of this study was to determine the effectiveness of photo comics media on the learning outcomes of fifth grade elementary school students.The research method used is a quasi-experimental design with Pretest-Posttest Control Group Design. The subjects in this study were 51 fifth grade elementary school students in Godean Sleman District. The data was obtained through the implementation of online learning. In the experimental group, students were given the treatment to do learning using photo comics, while in the control group there was no treatment. The data collection technique used a written test in the form of multiple choice questions. The data obtained were analyzed using an independent t-test.The results showed that the value of ttable = 2.00958 and tcount = 2.258, thus tcount ttable 2,258 2,005. Based on these results it can be concluded that Ho is rejected and Ha is accepted. This shows that learning to use the help of photo comic media has an effect on improving the learning outcomes of fifth grade elementary school students.